Interfacial reactions in graphene oxide/polyacrylonitrile composite films. Issue 2 (1st February 2021) - Gao, Aijun; Xu, Dehua; Li, Changqing; Wang, Yu; Xu, Lianghua
ABSTRACT: This study investigated the role of polyacrylonitrile (PAN) in graphene macroassemblies. Samples were characterized by differential scanning calorimetry, thermogravimetric analysis, X-ray diffraction, Raman spectroscopy, and X-ray photoelectron spectrometry. The results show that PAN can be used as a 'coupling agent' of graphene oxide (GO). During heat treatment, the carboxyl group (-COOH) on GO sheets nucleophilically attacks the carbon of the cyano group (-CN) to initiate cyclization of the PAN, which in turn connects GO to PAN. Meanwhile, the oxygen in GO promotes PAN dehydrogenation. As the temperature increases continuously, crosslinking occurs between PAN molecules and those PAN connected to GO, and between the edges of GO. This promotes formation of larger conjugate planes. Larger graphite crystallites are formed owing to π–π stacking interaction. The extent of reaction between GO and PAN varies with different PAN content. A low PAN content primarily acts as a coupling agent. The graphite crystallites size increases as the PAN content increases, with the largest crystallite size obtained in the presence of 17 wt% PAN. As PAN content increases further, large amounts of PAN self-react and carbonize to form small graphite crystallites. The average size of graphite crystallites therefore decreases with increasing PAN content. Graphical Abstract: uf0001